2019
DOI: 10.1111/apa.14702
|View full text |Cite
|
Sign up to set email alerts
|

Review shows that donor milk does not promote the growth and development of preterm infants as well as maternal milk

Abstract: Aim This nonsystematic review examined differences in the composition of raw maternal breastmilk and pasteurised donor milk and possible health effects on preterm infants. Methods We searched PubMed up to July 2018 for studies published in English that focused on four comparisons as follows: raw maternal milk versus donor milk, human milk before and after Holder pasteurisation, milk from mothers who delivered preterm and at term and milk collected during early and late lactation. We also searched for possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 63 publications
2
37
0
1
Order By: Relevance
“…Premature infant care is in continuous progress; however, optimal feeding is still a challenge due to specific requirements and most extremely premature babies suffer postnatal growth retardation [8]. Breastfeeding and human milk are the gold standards for infant feeding and nutrition and are recommended from the first hour of life to the first six months exclusively, with complementary solid foods being introduced up to two years of age or beyond [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Premature infant care is in continuous progress; however, optimal feeding is still a challenge due to specific requirements and most extremely premature babies suffer postnatal growth retardation [8]. Breastfeeding and human milk are the gold standards for infant feeding and nutrition and are recommended from the first hour of life to the first six months exclusively, with complementary solid foods being introduced up to two years of age or beyond [9].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding and human milk are the gold standards for infant feeding and nutrition and are recommended from the first hour of life to the first six months exclusively, with complementary solid foods being introduced up to two years of age or beyond [9]. Breast milk contains all the compounds and energy necessary for the correct development and growth of infant during the early stages of life and is associated with the promotion of neurodevelopment, protective effects against necrotizing enterocolitis (NEC), and reductions in late onset sepsis and retinopathy severity in prematurity [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review by Hård et al. showed that pasteurised donor milk did not promote the growth and development of very preterm infants as effectively as raw maternal milk. Both were associated with a lower incidence of necrotising enterocolitis than preterm formula, but high‐dose feeding with maternal milk also reduced the risk of other morbidities.…”
Section: Donor Milk Did Not Promote the Growth And Development Of Prementioning
confidence: 99%